Childhood sexual trauma and subsequent parenting beliefs and behaviors. (June 2015) - Zvara, B.J.; Mills-Koonce, W.R.; Appleyard Carmody, K.; Cox, M.; ,
Abstract: Using propensity-matched controls, the present study examines the long-term adjustment of women reporting childhood sexual trauma (CST) at or before the age of 14 in terms of parenting efficacy and parenting behavior. Data for these analyses were obtained from mother reports and from observational protocols from a longitudinal study of low-income, rural families. The novel use of propensity-matched controls to create a control group matched on family of origin variables provides evidence that when women with CST are compared with the matched comparison women, females who experienced CST show poorer functioning across multiple domains of parenting (sensitivity, harsh intrusiveness, boundary dissolution), but not in parenting efficacy. Follow-up moderation analyses suggest that the potential effects of trauma on parenting behaviors are not attenuated by protective factors such as higher income, higher education, or stable adult relationships. Implications for interventions with childhood sexual trauma histories and directions for future study are proposed.